Морфологічні особливості листків видів роду Tilia L. (секція Anastraea Engl.) - Tsarenko, O.M.; Vakulenko, T.B.; Doroshenko, O.K.; Karpenko, N.I. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2016)
The macro- and micromorphological features of leaves of 8 species, which represented 11 intraspecific taxa of the genus Tilia L., belonging to the section Anastraea Engl. (native or introducers species of Ukrainian flora) are studied. It was confirmed that the shape and dimensions of the leaf blade, and the teeth of the edges as well as the tops, peculiarities venation, dimensions of petioles it is useful to consider as a significant features for identification of the species composition. The peculiarities of the leaf pubescence and the structure of glandular hairs as well as all identified covering trichomes (simple and stellate), and their place on the blade (interveinal surface, along the veins, in the corners of the large veins , etc.) are investigated and described. It was found that these characteristics in combination with characteristics mentioned above, are also important for determination of species and infraspecific rank taxa of Anastraea section. Taking into account peculiarities of pubescence of the leaves it was correctly united taxa in section Anastraea.